MATHEMATICAL MODELS PREDICTING LEUKOPENIA AND NEUTROPENIA IN PATIENTS WITH CHRONIC HEPATITIS C IN THE BACKGROUND INTERFERONCONTAINING SCHEMES - I. G. Bakulin; N. Kh. Dianova; Yu. G. Sandler; M. Yu. Prostov (Архивъ внутренней медицины)
Currently in the Russian Federation or chronic hepatitis C (CHC) are still relevant Interferon-based regimens. The purpose of this study is to investigate the influence of baseline characteristics and prognosis of the patient HCV genotype 1 for the development  of leukopenia (LP) and neutropenia  (NP). We investigated  factors such as sex, age, body mass index (BMI), viral load, genotype  of Interleukin-28 B (IL-28B),  the initial level of leukocytes and neutrophils,  alanine aminotransferase (ALT), fibrosis, duration  of infection, presence  of previous therapy.  Absolute values of leukocytes  and neutrophils  were analyzed on 4, 12, 24, 48 weeks of therapy,  and at 4, 12, 24 weeks after antiviral treatment with protease  inhibitors (PI) 1 and 2 generation. Prognostic criteria were identified, indicating the possible development  of the LP and NP expressed during treatment with interferon: female  gender,  low initial load, TT-genotype of IL-28B, the  initial level of white  blood cells and neutrophils  below 5,7×109/L and 3,4×109/L, respectively. Mathematical  models predicting the onset of LP and NP, formalized in the form of decision trees were also constructed. These models have shown the greatest potential for practical use in view of highest accuracy and reliability.